Preliminary Study on the Effect of Ethylene Diamine- n, n-diacetic Acid on Methane Gas Production Rate from Cow Manure - Nwokem N Calvin; Gimba C. Emmanuel; Ndukwe G. Iloegbunam; Ella E. Elijah (Aceh International Journal of Science and Technology, 2014)
In an effort to improve methane gas production rate from cattle slurry; ethylene diamine- N, N-diacetic acid chelating ligand was introduced into the digester system. Experimental analysis involving the determination of trace metals, pH and methane gas yield, were carried out with the use of the Flame Atomic Absorption Spectrophotometer and Biogas5000 analyser. The results showed that there was an increase in the pH of the system; the amount of methane gas yield equally increased by 12% and the Hydraulic Retention Time decreased from 50 days to 25 days on addition of ethylene diamine- N, N-diacetic acid chelating ligand. Also, increasing the concentration of the chelating ligand further decreased the HRT of the digester system from 25 days to 19days. Concentration of trace metals like Iron, Cobalt and Nickel within the digester system ranged from 0.001-0.050 mg/L; these metals reacted with ethylene diamine- N, N-diacetic acid chelating ligand to form metal chelates. The metal chelate formed resulted in the catalysis of the hydrolysis stage (which is the rate determining step) of the anaerobic digestion process. Thus, the decrease in HRT was due to the metal chelate catalysis of the hydrolysis stage of the anaerobic digestion process were the metal chelate formation served as the driving force in the solvolysis process.